2013
DOI: 10.1007/s00300-013-1396-3
|View full text |Cite
|
Sign up to set email alerts
|

The relative contributions of biological and abiotic processes to carbon dynamics in subarctic sea ice

Abstract: Knowledge on the relative effects of biological activity and precipitation/dissolution of calcium carbonate (CaCO 3 ) in influencing the air-ice CO 2 exchange in sea-icecovered season is currently lacking. Furthermore, the spatial and temporal occurrence of CaCO 3 and other biogeochemical parameters in sea ice are still not well described. Here we investigated autotrophic and heterotrophic activity as well as the precipitation/dissolution of CaCO 3 in subarctic sea ice in South West Greenland. Integrated over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 93 publications
1
55
1
Order By: Relevance
“…There are several reports of ikaite precipitation in Arctic sea ice Rysgaard et al, 2012aRysgaard et al, , 2013Geilfus et al, 2013a, b;Søgaard et al, 2013). In this study, however, only a few crystals were observed and they dissolved within minutes after melting the sea ice.…”
Section: Discussioncontrasting
confidence: 66%
“…There are several reports of ikaite precipitation in Arctic sea ice Rysgaard et al, 2012aRysgaard et al, , 2013Geilfus et al, 2013a, b;Søgaard et al, 2013). In this study, however, only a few crystals were observed and they dissolved within minutes after melting the sea ice.…”
Section: Discussioncontrasting
confidence: 66%
“…As a result, the concentration of dissolved salts, including inorganic carbon, increases within the brine and promotes the precipitation of calcium carbonate crystals such as ikaite (CaCO 3 q 6H 2 O) (Marion, 2001). These crystals have been reported in both natural (Dieckmann et al, 2008;Nomura et al, 2013;Søgaard et al, 2013) and experimental sea ice (Geilfus et al, 2013b;Rysgaard et al, 2014) and have been suggested to be a key component of the carbonate system Fransson et al, 2013;.…”
mentioning
confidence: 80%
“…the formation/dissolution of calcium carbonate (CaCO 3 · 6 H 2 O) within brine (Dieckmann et al, 2008;Fischer et al, 2013;Marion, 2001;Papadimitriou et al, 2004;Rysgaard et al, 2013), which leads to an increase/decrease in brine pCO 2 , thus changing the potential for CO 2 exchanges at the ice surface (Geilfus et al, 2012;Miller et al, 2011b;Sogaard et al, 2013); 3. CaCO 3 · 6 H 2 O being observed in brine-soaked snow at the snow-ice interface Nomura et al, 2013).…”
Section: Thermochemical Carbon Processes In the Icementioning
confidence: 99%